375 تعزيز دور المنطقة الاقتصادية لقناة السويس لبناء قاعدة صناعية لمنتجات عالية التكنولوچيا : Enhancing The Role of the Suez Canal Economic Zone to Build an Industries Base for High-Tech - إجلال راتب حسين صالح، محمد عبد الشفيع وأخرون (معهد التخطيط القومي, 2026)
يتناول البحث دور المناطق الاقتصادية والتكنولوجية الخاصة في دعم التنمية الصناعية وجذب الاستثمارات. ويركز على المنطقة الاقتصادية لقناة السويس كنموذج لتعزيز التنافسية وتوطين الصناعات المتقدمة. كما يستعرض التجارب الدولية الناجحة والعوامل المؤثرة في نجاح المناطق الاقتصادية الخاصة. ويحلل تطورات الاستثمار الأجنبي المباشر والبنية التحتية والتحول الرقمي بالمنطقة الاقتصادية لقناة السويس. ويقدم مجموعة من السياسات والتوصيات لدعم التنمية المستدامة وتعميق الاندماج في الاقتصاد العالمي. The research explores the strategic role of Special Economic and Technological Zones in supporting economic transformation and industrial competitiveness. It focuses on the Suez Canal Economic Zone as a key hub for attracting foreign investment and high-tech industries. The study reviews international experiences and evaluates the zone’s infrastructure, digital transformation, and smart port development. It also analyzes foreign direct investment trends and opportunities in high-tech, green hydrogen, and green ammonia industries. The research presents policy recommendations to strengthen sustainable development and global economic integration.